Optical Fingerprints of Si Honeycomb Chains and Atomic Gold Wires on the Si(111)-(5x2)-Au Surface - MCGILP, JOHN (My University, 2013)
The intensively studied Si(111)-(5×2)-Au surface is reexamined using reflectance anisotropy spectroscopy and density functional theory simulations. We identify distinctive spectral features relating directly to local structural motifs such as Si honeycomb chains and atomic gold wires that are commonly found on Au-reconstructed vicinal Si(111) surfaces. Optical signatures of chain dimerization, responsible for the observed (×2) periodicity, are identified. The optical response, together with STM simulations and first-principles total-energy calculations, exclude the new structure proposed very recently based on the reflection high-energy electron diffraction technique analysis of Abukawa and Nishigaya [Phys. Rev. Lett. 110, 036102 (2013)] and provide strong support for the Si honeycomb chain with the triple Au chain model of Erwin et al. [Phys. Rev. B 80, 155409 (2009)]. This is a promising approach for screening possible models of complex anisotropic surface structures.
PUBLISHED
Keywords: Physics; Nanoscience & Materials